Association of level serum 25-hydroxy vitamin D in benign and malignant breast disease in a tertiary care center in North India - Srivastava, Vaibhav; Kumar, Shirish; Ahmad, Shabi; Singh, Vikram; Rai, Nandan; Singh, Rohit (International Surgery Journal, 2020)
Background: The study was to compare 25-hydroxy vitamin D levels in women with benign and malignant breast disease patients to the age-matched controls in a tertiary care center in North India. Methods: This was a prospective study carried out in the Department of Surgery, S.R.N. Hospital associated with M.L.N. Medical College, Allahabad. The levels of vitamin D are measured by electrochemiluminescence and the serum levels divided into normal, mild, moderate, and severe vitamin D deficiency. Results: Overall 60 patients were included. 30 was having malignant breast disease and 30 having benign breast disease. On comparing the mean value of serum vitamin D level between malignant breast disease and controls, the serum vitamin D level was found to be lesser in the former group and the difference was highly significant. On comparing the mean value of serum vitamin D level between benign breast disease and controls, the serum vitamin D level was found to be elevated in the former group, the difference was nonsignificant. Conclusions: Our study supports the hypothesis that vitamin D deficiency is an important risk factor in the development of malignant breast disease. The study was also concluded that vitamin D is not associated with the etiogenesis of benign breast diseases. There is also a possibility of using 25-hydroxy vitamin D as an adjuvant therapy during the treatment of breast malignancy.